2021
DOI: 10.1038/s41422-021-00495-9
|View full text |Cite|
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein interacts with and activates TLR41

Abstract: Dear Editor, Accumulating clinical data suggest the main causes of death by COVID-19 include respiratory failure and the onset of sepsis. 1 Importantly, sepsis has been observed in nearly all deceased patients. 2-5 It remains elusive how SARS-CoV-2 infection results in viral sepsis in humans. Toll-like receptor 4 (TLR4) mediates antigram-negative bacterial immune responses by recognizing lipopolysaccharide (LPS) from bacteria. 6 We recently found that SARS-CoV-2 infection provoked an anti-bacterial like respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
283
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(303 citation statements)
references
References 13 publications
12
283
3
5
Order By: Relevance
“…Although both NL63 and SARS-CoV-2 (CoV-2) use ACE2 as their receptor to infect host cells, NL63 is much less virulent than CoV-2, indicating that tissue tropism may not account for their dramatic virulent differences. Because CoV-2 but not NL63 causes severe cytokine storm (Mehta et al, 2020), and two independent studies have shown that CoV-2 Spike protein (CoV-2-S) activates TLR4/NF-kB signaling in macrophages (Zhao et al, 2021), we then suspected that CoV-2-S and NL63-S might have different effects on TLR4/NF-kB signaling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both NL63 and SARS-CoV-2 (CoV-2) use ACE2 as their receptor to infect host cells, NL63 is much less virulent than CoV-2, indicating that tissue tropism may not account for their dramatic virulent differences. Because CoV-2 but not NL63 causes severe cytokine storm (Mehta et al, 2020), and two independent studies have shown that CoV-2 Spike protein (CoV-2-S) activates TLR4/NF-kB signaling in macrophages (Zhao et al, 2021), we then suspected that CoV-2-S and NL63-S might have different effects on TLR4/NF-kB signaling.…”
Section: Resultsmentioning
confidence: 99%
“…In toxic shock syndrome, this motif interacts with both T cell receptor (TCR) and CD28 to elicit T lymphocyte activation (Cheng et al, 2020). Two independent in vitro studies have shown CoV-2-S to activate TLR4 innate immune signaling in cultured macrophages (Shirato and Kizaki, 2021; Zhao et al, 2021). These studies highlight CoV-2-S as a potent culprit that could possibly induce systemic inflammation; however, the underlying molecular mechanism is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports using non-soluble SARS-CoV-2 trimeric spike (S) glycoprotein 10 and purified S1 subunit produced in E.coli 11 suggest that the S protein activates inflammation in macrophages. Prefusion trimeric S is cleaved by cellular proteases 12 that dissociate the S1 subunit during virion assembly 13 or after engagement of the ACE2 receptor 14 .…”
Section: Resultsmentioning
confidence: 99%
“…By understanding the mechanisms by which the virus-induced "cytokine storm" is mitigated, we expect to discover therapeutic targets in the influenza model that will be applicable also to patients with severe SARS-CoV-2 and other virus-induced lung diseases. A recent study reported that the SARS-CoV-2 trimeric spike (S) protein directly interacted with and activated TLR4 in vitro in human and murine macrophagelike cell lines, and in bone marrow-derived macrophages from wildtype, but not TLR4 -/-, mice (143). Moreover, treatment of cells with Resatorvid (TAK-242), that blocks MyD88 interaction with TLR4 (31), also blocked S protein-induced Il1b mRNA (143).…”
Section: Discussionmentioning
confidence: 99%